Polar Cap Absorption in Antarctica in 1967 - Khodzha-Akhmedov,Ch. L. (1973)
Polar cap absorption (PCA) was investigated from January to May of 1967. It was found that PCA follows a daily course, generating the most radio noise at midday when the sun's altitude is highest. During absorptive periods, radio communications were disturbed and, in some cases, completely absent. However, data contradicting this observation are reported. In spite of this, the absorptive region was formed below the region of scattering. Trans. of Sovetskaya Antarkticheskaya Ekspeditsiya. Trudy, v47 p162-70, n.d.